Long-term Use of Continuous Subcutaneous Hydrocortisone Infusion Therapy in Patients with Congenital Adrenal Hyperplasia - Mallappa, Ashwini (Clin Endocrinol (Oxf), 2018)
BACKGROUND: In a phase 2 short-term (6 months) study of patients with congenital adrenal hyperplasia (CAH), continuous subcutaneous hydrocortisone infusion (CSHI) was found to be a safe, effective, and well-tolerated method of replacing cortisol with improved disease and patient related outcomes. OBJECTIVE: Evaluate the safety and efficacy of long-term CSHI. DESIGN: Single centre, open label, phase 2 extension study. PATIENTS: Five adults with classic CAH. MEASUREMENTS: Biomarkers of disease control, metabolic indices and health-related quality-of-life (HRQoL) estimates. RESULTS: Six of eight patients chose to continue on long-term CSHI therapy. Compared to baseline, eighteen months of CSHI resulted in decreased (P = 0.043) 0700–hour ACTH, 17-hydroxyprogesterone, androstenedione, and progesterone; increased whole-body lean mass (P = 0.024); and improved HRQoL, especially symptoms of adrenal insufficiency (P = 0.003). Findings at six and eighteen months did not differ and improvements achieved in androgen control, lean body mass and HRQoL after six months of CSHI were maintained at eighteen months. The hydrocortisone dose appeared to decrease with time [6 vs. 18 months: 38.3 ± 8.8 vs. 33.6 ± 12.2 mg/day (P = 0.062)], especially in women receiving oral contraceptives. Reduction of testicular adrenal rest and adrenal size observed at 6 months remained stable. In one patient, an adrenal adenoma continually decreased over time. Subjective improvement in hirsutism was reported. CONCLUSIONS: Long-term use of CSHI is a safe and well-tolerated treatment option in a select set of adults with classic CAH. Improvements observed short-term in disease control and subjective health status continued long-term.